2005
DOI: 10.1073/pnas.0409470102
|View full text |Cite
|
Sign up to set email alerts
|

Calling for help is independently modulated by brain systems underlying goal-directed behavior and threat perception

Abstract: In primates, during times of need, calling for help is a universal experience. Calling for help recruits social support and promotes survival. However, calling for help also can attract predators, and it is adaptive to inhibit calls for help when a potential threat is perceived. Based on this, we hypothesized that individual differences in calling for help would be related to the activity of brain systems that mediate goal-directed behavior and the detection of threat. By using high-resolution positron emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…Increased cooing in adulthood could be related to the increase in anxiety-like behaviors reported, a finding consistent with the classification of “coos” in the basic measures of primate anxiety/displacement behaviors (Hinde & Rowell, 1962; Jiang et al, 2013; Mcfarland, 1966; Redican, 1975). This increase in cooing behavior may have resulted from a decrease in amygdala drive after the lack of PRh inputs since amygdala activity has been negatively correlated with frequency of separation-induced coo vocalization in adolescent monkeys (Fox et al, 2005) and amygdala lesions increase coos (Kalin, Shelton, & Davidson, 2004; Kalin et al, 2001; Raper et al, 2013a)…”
Section: Discussionmentioning
confidence: 99%
“…Increased cooing in adulthood could be related to the increase in anxiety-like behaviors reported, a finding consistent with the classification of “coos” in the basic measures of primate anxiety/displacement behaviors (Hinde & Rowell, 1962; Jiang et al, 2013; Mcfarland, 1966; Redican, 1975). This increase in cooing behavior may have resulted from a decrease in amygdala drive after the lack of PRh inputs since amygdala activity has been negatively correlated with frequency of separation-induced coo vocalization in adolescent monkeys (Fox et al, 2005) and amygdala lesions increase coos (Kalin, Shelton, & Davidson, 2004; Kalin et al, 2001; Raper et al, 2013a)…”
Section: Discussionmentioning
confidence: 99%
“…We have established a non-human primate model of childhood AT, facilitating the identification of the neural mechanisms underlying the development of early life anxiety. In rhesus monkeys, AT is assessed as a composite of threat-induced freezing behavior, inhibition of vocalizations and increased plasma cortisol levels (4, 5). We previously demonstrated that metabolic activity in the central nucleus (Ce) of the amygdala, indexed using high-resolution [ 18 F]-fluorodeoxyglucose-positron emission tomography (FDG-PET), strongly predicts individual differences in AT (6, 7).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the impacts of different types of ethologically relevant stressors on behavioral, neurochemical, physiological and brain functional responses have been well characterized in this species. [26][27][28] We have been performing highresolution FDG microPET scans in rhesus monkeys to explore the relation between patterns of brain metabolic activity and individual differences in anxiety-related traits. For example, we previously demonstrated that when threatened by a human intruder for a 30-min period, monkeys' individual differences in metabolic activity in the bed nucleus of the stria terminalis (BNST) are strongly predictive of individual differences in monkeys' anxiety-related freezing responses.…”
Section: Introductionmentioning
confidence: 99%